Hydrothermal fluids and where to find them: using seismic attenuation and anisotropy to map fluids beneath Uturuncu volcano, Bolivia - Hudson, TS; Kendall, JM; Blundy, JD; Pritchard, ME; MacQueen, P; Wei, SS; Gottsmann, JH; Lapins, S (American Geophysical Union, 2023)
Mapping fluid accumulation in the crust is pertinent for numerous applications including volcanic hazard assessment, geothermal energy generation, and mineral exploration. Here, we use seismic attenuation tomography to map the distribution of fluids in the crust below Uturuncu volcano, Bolivia. Seismic P wave and S wave attenuation, as well as their ratio (QP/QS), constrain where the crust is partially and fully fluid-saturated. Seismic anisotropy observations further constrain the mechanism by which the fluids accumulate, predominantly along aligned faults and fractures in this case. Furthermore, subsurface pressure-temperature profiles and conductivity data allow us to identify the most likely fluid composition. We identify shallow regions of both dry and H2O/brine-saturated crust, as well as a deeper supercritical H2O/brine column directly beneath Uturuncu. Our observations provide a greater understanding of Uturuncu's transcrustal hydrothermal system, and act as an example of how such methods could be applied to map crustal fluid pathways and hydrothermal/geothermal systems elsewhere.